Chiral Spin-Orbital Liquids with Nodal Lines - Natori, W. M.H.; Andrade, E. C. [UNESP]; Miranda, E.; Pereira, R. G. (American Physical Society (APS), 2016)
Strongly correlated materials with strong spin-orbit coupling hold promise for realizing topological phases with fractionalized excitations. Here, we propose a chiral spin-orbital liquid as a stable phase of a realistic model for heavy-element double perovskites. This spin liquid state has Majorana fermion excitations with a gapless spectrum characterized by nodal lines along the edges of the Brillouin zone. We show that the nodal lines are topological defects of a non-Abelian Berry connection and that the system exhibits dispersing surface states. We discuss some experimental signatures of this state and compare them with properties of the spin liquid candidate Ba2YMoO6.